Estimation of the transformer parameters from nameplate data using turbulent flow of water optimization technique - Amir Yassin Hassan; Mokhtar Said; Saber Mohamed Saleh Salem (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The mismatch between the transformer and its model leads to deviation of the results during the study of the different abnormal phenomena. This paper presents an optimization technique using transformer nameplate data to minimize the difference in the estimation of the parameters between the model and the actual transformer data. The turbulent flow of water through a narrow path (TFWO) in a circular form technique is used for the optimization of the transformer parameters. The optimization algorithms are used in extracting the parameters of the different rating of transformers, this technique needs an objective function for performing the optimization process. Minimizing the sum of square error (SSE) is the objective function of the optimizer technique. The SSE function includes the summation of the square error for the primary current and secondary current and voltage referring to the primary. The proposed optimization transformer parameters evaluation based on the nameplate data is accurate and fulfilled compared with the other methods.